Resilient Urban Development in Sudan: Integrating Socioeconomic and Technological Factors for Sustainable Energy in Omdurman City, Sudan - Elhassan , Zeinab Abdallah Mohammed; Sirror , Hala; Hamid , Malathe; Ali , Hend (Journal of Ecohumanism, 2025)
This study evaluates the integration of photovoltaic (PV) systems in Omdurman, specifically focusing on Omdurman Althawra, to enhance urban design and architectural planning for domestic use. By analyzing data from blocks 10 and 18, the research incorporates the experiences of residents to identify effective strategies for implementing building-integrated photovoltaics (BIPV). The methodology includes a comprehensive historical and geographical analysis to understand existing services and infrastructure, as well as the roles of various stakeholders, including authorities, communities, and homeowners in the development of PV systems. The findings highlight the challenges of providing essential services in a rapidly urbanizing environment while addressing energy demands through renewable solutions. The study emphasizes the importance of public policy and regional planning in fostering sustainable energy practices that meet the needs of Omdurman’s population. By documenting daily observations and opinions from residents, this research aligns technological, social, legal, and economic factors with environmental considerations to propose a framework for future energy-efficient urban development in Omdurman. Ultimately, the study aims to inform decision-making processes regarding health, renewable energy, and low-energy building designs that leverage rooftop PV systems as a clean energy solution for urban planning in developing regions like Khartoum state.